Porous organic materials offer vast future opportunities - Tianyu Liu (Nature Portfolio, 2020)
In light of the surging research on porous organic materials, we herein discuss the key issues of their porous structures, surface properties, and end functions. We also present an outlook on emerging opportunities, new applications, and data science-assisted materials discovery.